Experimental study and regression modeling of tool wear in CNC turning operation using soybean based cutting fluid / Posinasetti Nageswara Rao, Julie Zhang and Marry Eckman - Nageswara Rao, Posinasetti; Zhang, Julie; Eckman, Marry (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2013)
Traditionally petroleum based fluids are widely used in the manufacturing industry. However they are environmentally more harmful as well as cause significant problems to the operators. This paper presents a case study that uses an environmentally friendly soybean based cutting fluid. This experimental study compared the tool wear with dry cutting, using the soybean based cutting fluid and a petroleum based cutting fluid at manufacturer suggested cutting fluid concentrations in a CNC turning operation. It was found that the soybean based cutting fluid provided a comparable performance as that of the petroleum cutting fluid in controlling tool wear. Further experiments were conducted with the soybean based cutting fluid at different concentrations. From the tool wear data collected at different soybean based cutting fluid concentrations a linear regression model was built to predict the tool wear based on the soybean cutting fluid concentration. The manufacturing professionals can utilize this regression model, to analyze the machining process with a view to maximizing the tool life and minimizing the machining cost.